Disappearance of a scribe - Stabenow, Dana (Stabenow, Dana. Eye of Isis., 2022)
After two Alexandrian fishermen discover a skeleton anchored by a cement weight, Queen Cleopatra charges Tetisheri, her new Eye of Isis, to uncover the identities of the victim and the killers.